Tasybih dalam Mu’allaqoh Zuhair bin Abi Sulma: Kajian Balaghah dan Analisis - Amarulloh; Ahmad Dardiri; Raswan; Achmad Fudhaili (Indo Publishing, 2025)
This research aims to analyze the use of tasybih in Mu'allaqah Zuhair bin Abi Sulma using a balaghah analysis approach. The method used is qualitative research with a library research design. Primary data is in the form of 65 pieces in Mu'allaqah Zuhair bin Abi Sulma, while secondary data comes from literature discussing the science of balaghah, especially the science of bayan. The data collection technique was carried out using reading and writing techniques, while data analysis used a qualitative descriptive method with the Miles and Huberman interactive analysis model, which includes data reduction, data presentation and drawing conclusions. The research results showed that Zuhair bin Abi Sulma used various types of tasybih, such as mursal mufashal tasybih, baligh tasybih, and dhimni tasybih. Tasybih mursal mufashal is used to clarify the meaning by mentioning the tasybih instrument explicitly, while tasybih baligh provides a stronger effect by omitting the tasybih instrument. Meanwhile, dhimni tasybih present implied meanings that require deeper interpretation. Analysis found 10 baits in Mu'allaqah that contained tashbih elements. The use of prayer beads not only functions as a stylistic tool, but also strengthens the aesthetic and rhetorical values ​​in poetry, reflecting the poet's wisdom and moral message.